Modélisation et simulation de l’effet des bras morts sur la conductivité électrique dans un réseau de percolation. Cas d’un matériau polymère isolant. - MEBARKI Benziane (My University, 2014)
The electrical conductivity of organic insulating materials has been investigated using several theoretical models combining the percolation approach. The dead ends of the infinite cluster do not contribute generally to the electrical conduction in the presence of a weak electric field. We show in the first part, referring to the percolation approach, that during the application of a high electric field; the dead ends decrease the electrical conductivity according to an exponential law with a negative exponent, in dependence to the energy distribution of the sites, the correlation length of the clusters, and the length of the dead ends. In the second part, we check by simulation the effects of these dead ends on the electrical conductivity.